The Return of the Prodigy Son: Do Return Migrants Make Better Leaders? - Marion Mercier (Institute for the Study of Labor (IZA), 2013)
This paper investigates the impact of political leaders' migration experience on the quality of their leadership. We build up an original database on the personal background of 932 politicians who were at the head of the executive power in a developing country over the 1960-2004 period. We put forward a positive effect of the leader having studied abroad on the level of democracy in his country during his tenure. This effect is shown to be independent from the leader's education level, as well as from his profession. Moreover, it is mainly driven by countries with a poor initial level of democracy. These results are confirmed by various robustness tests. They propose a new channel through which migration may affect politics in the sending countries, namely the emergence of the elites.
Keywords: O11; E02; F22; N40; 330; political leaders; migration; democracy; developing countries